2016
DOI: 10.1038/srep23781
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation of the liver: is there a safe limit to the ablation volume?

Abstract: Irreversible electroporation is a fast-growing liver ablation technique. Although safety has been well documented in small ablations, our aim is to assess its safety and feasibility when a large portion of liver is ablated. Eighty-seven mice were subjected to high voltage pulses directly delivered across parallel plate electrodes comprising around 40% of mouse liver. One group consisted in 55 athymic-nude, in which a tumor from the KM12C cell line was grown and the other thirty-two C57-Bl6 non-tumoral mice. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Cardiac arrhythmias rarely impair completion of an IRE procedure, as was the case in our three instances of atrial fibrillation which were all either self-limiting or medically managed [19]. Ablation of large tumour volumes (40% of liver) has been shown in an animal model to induce alterations in serum potassium levels due to ionic shifts with nanopore formation resulting in the potential for electrocardiogram arrhythmias, but this mechanism is not felt to be applicable in this study as lesional volume was considerably smaller [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrhythmias rarely impair completion of an IRE procedure, as was the case in our three instances of atrial fibrillation which were all either self-limiting or medically managed [19]. Ablation of large tumour volumes (40% of liver) has been shown in an animal model to induce alterations in serum potassium levels due to ionic shifts with nanopore formation resulting in the potential for electrocardiogram arrhythmias, but this mechanism is not felt to be applicable in this study as lesional volume was considerably smaller [20].…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 For instance, our previous IRE protocol with plate electrodes lasted for 100 seconds (90-100 pulses at a frequency of 1 Hz). 16 , 31 Our protocol IRE lasted 100 seconds, without pauses. However, pauses can be reduced in case the TW values obtained in this preliminary study are set in this range of time, in future essays with bigger sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 15 In this study we showed that even with high electrical fields (up to 2000 V/cm) complete eradication of the tumour was infrequent even when massive destruction of nearby healthy hepatic tissue was present (expressed by life-threating ionic imbalances). 16 …”
Section: Introductionmentioning
confidence: 99%
“…IRE is practical and safe for ablation in hepatic adenocarcinoma [29]. In a prospective, nonrandomized study, Cheung et al [30].…”
Section: Discussionmentioning
confidence: 99%